Chemical Characterization and Antioxidant Activity of Ethanol and n-Hexane Extract of Pangi Leaves (Pangium edule Reinw. ex Blume) - Jonathan Cavin Ezra Sinaga; Hartanto Bisma; Josua Tampara; Max Revolta John Runtuwene; Vanda Selvana Kamu; Dewa Gede Katja; Lidya Irma Momuat (Jurnal Ilmiah Sains, 2026)
Pangi leaves (Pangium edule Reinw. ex Blume) are a type of plant that is often consumed by the people of North Sulawesi. This study aims to determine the total phenolic content, chemical characterization using GC-MS and FTIR, and antioxidant activity of pangi leaves using solvents that have different polarities. Total phenolics were measured using the Folin-Ciocalteu method. Antioxidant activity was evaluated using the DPPH method. The total phenolic content showed that the ethanol extract had a content of 17.94 μg/mL and the n-hexane extract was 12.94 μg/mL. The ethanol extract (IC50 = 656.39 μg/mL) had better antioxidant activity than the n-hexane extract (IC50 = 1991.76 μg/mL). Based on the GCMS results, 19 compounds were obtained from the ethanol extract and 16 compounds from the n-hexane extract. The FTIR results of the ethanol extract and n-hexane extract have functional groups -OH, aliphatic C-H, C=C (alkene or aromatic), C=O, and C-O. Keywords: Antioxidants; GCMS analysis; FTIR analysis; pangi leaves; DPPH